2015
DOI: 10.1016/j.ijsolstr.2015.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Analytical investigation of structurally stable configurations in shape memory alloy-actuated plates

Abstract: a b s t r a c tStrains produced by active materials embedded in plates have been extensively used to manipulate the shape of surface-like engineering structures. Shape memory alloys (SMAs) are active materials that provide a significant amount of strain under large stresses, a characteristic of great utility in such morphing structures. In this work, an analytical approach to approximate the deformation of plates with SMA constituents is developed via the Rayleigh-Ritz method. An additive set of kinematically … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(7 citation statements)
references
References 68 publications
0
7
0
Order By: Relevance
“…(1-7) = 0, which is subsequently solved numerically using a Newton-type scheme. We note that Betts et al 39 and Hernandez et al 40 have reported success in obtaining closed form solutions for specific geometry and constitutive properties. Second variations are used to determine the stability of each of the equilibria as per the procedure described in Hyer's seminal work.…”
mentioning
confidence: 81%
“…(1-7) = 0, which is subsequently solved numerically using a Newton-type scheme. We note that Betts et al 39 and Hernandez et al 40 have reported success in obtaining closed form solutions for specific geometry and constitutive properties. Second variations are used to determine the stability of each of the equilibria as per the procedure described in Hyer's seminal work.…”
mentioning
confidence: 81%
“…(11), and phase-transition modulus equation, Eq. (18). A uniform tensile SMA bar, shown in Figure 2(a), is numerically simulated to verify the MATLAB program.…”
Section: Applicationsmentioning
confidence: 99%
“…Some researchers [15][16][17] implemented finite element analysis on SMA structures based on the secondary development functions of ANSYS. Many researchers [18][19][20][21] implemented finite element simulation on SMA structures using the secondary development functions of ABAQUS. Although some universal finite element software can simulate the thermo-mechanical behaviors of SMA based on their secondary development functions, the problems of convergence often occur when a SMA structure undergoes large and uneven deformations.…”
Section: Introductionmentioning
confidence: 99%
“…The two main components of the adaptive skins are a flexible panel and SMA wires. The capability of SMAs in wire form to provide controlled deformation to plates and shell systems has been demonstrated in previous works addressing self-foldable origami sheets (Halbert et al, 2016;Lee et al, 2013;Peraza Hernandez et al, 2014, compliant mechanisms Hwang and Higuchi, 2015), and multistable plates (Dano and Hyer, 2003;Peraza Hernandez et al, 2015); hence, SMAs are expected to be a viable option for panel-based adaptive skins. Figure 1(a) shows the working principle of the presented adaptive skins.…”
Section: Introductionmentioning
confidence: 96%